No signs of star formation being regulated in the most luminous quasars at z ∼ 2 with ALMA. Issue 1 (26th June 2019) - Schulze, Andreas; Silverman, John D; Daddi, Emanuele; Rujopakarn, Wiphu; Liu, Daizhong; Schramm, Malte; Mainieri, Vincenzo; Imanishi, Masatoshi; Hirschmann, Michaela; Jahnke, Knud
ABSTRACT: We present ALMA Band 7 observations at $850\, μ$ m of 20 luminous ($\log \, L_{\rm bol}\, \gt\, 46.9$ [erg s −1 ]) unobscured quasars at z ∼ 2. We detect continuum emission for 19/20 quasars. After subtracting an AGN contribution, we measure the total far-IR luminosity for 18 quasars, assuming a modified blackbody model, and attribute the emission as indicative of the star formation rate (SFR). Our sample can be characterized with a lognormal SFR distribution having a mean of 140 M⊙ yr −1 and a dispersion of 0.5 dex. Based on an inference of their stellar masses, the SFRs are similar, in both the mean and dispersion, with star-forming main-sequence galaxies at the equivalent epoch. Thus, there is no evidence for a systematic enhancement or suppression (i.e. regulation or quenching) of star formation in the hosts of the most luminous quasars at z ∼ 2. These results are consistent with the Magneticum cosmological simulation, while in disagreement with a widely recognized phenomenological model that predicts higher SFRs than observed here based on the high bolometric luminosities of this sample. Furthermore, there is only a weak relation between SFR and accretion rate on to their supermassive black holes both for average and individual measurements. We interpret these results as indicative of star formation and quasar accretion being fed from the available gas reservoir(s) in their host with a disconnect due to their different physical sizes, temporal scales, and means of gas processing.